1996
DOI: 10.1038/nm0696-696
|View full text |Cite|
|
Sign up to set email alerts
|

Intrathecal delivery of CNTF using encapsulated genetically modifiedxenogeneic cells in amyotrophic lateral sclerosis patients

Abstract: Neuronal growth factors hold promise for providing therapeutic benefits in various neurological disorders. As a means of ensuring adequate central nervous system delivery of growth factors and minimizing significant adverse side effects associated with systemic delivery methods, we have developed an ex vivo gene therapy approach for protein delivery using encapsulated genetically modified xenogeneic cells. Ciliary neurotrophic factor (CNTF) has been shown in various rodent models to reduce the motor neuron cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(169 citation statements)
references
References 16 publications
1
167
0
1
Order By: Relevance
“…[25][26][27] Cell encapsulation has also been employed to locally administer neurotrophic factors (CNTF and GDNF) locally in the central nervous system, both in pre-clinical and clinical studies, for the treatment of neurodegenerative disorders. [28][29][30] During reconstructive surgery, skin flaps are employed to cover wounds with poorly vascularized recipient beds where the damage is too extensive to permit repair using a skin graft. A skin flap is comprised of skin and subcutaneous tissue that is transferred from one area of the body to another, while maintaining an attachment to the body (vascular pedicle) for nourishment.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Cell encapsulation has also been employed to locally administer neurotrophic factors (CNTF and GDNF) locally in the central nervous system, both in pre-clinical and clinical studies, for the treatment of neurodegenerative disorders. [28][29][30] During reconstructive surgery, skin flaps are employed to cover wounds with poorly vascularized recipient beds where the damage is too extensive to permit repair using a skin graft. A skin flap is comprised of skin and subcutaneous tissue that is transferred from one area of the body to another, while maintaining an attachment to the body (vascular pedicle) for nourishment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these have been tested in therapeutic trials. In their investigation of gene-therapeutic modalities for motor neuron diseases, Aebischer et al 8 used encapsulated, genetically modified xenogeneic cells to deliver ciliary neurotrophic factor (CNTF) intrathecally into patients with ALS. Haase et al 9 demonstrated that adenovirus-mediated gene transfer of neurotrophin-3 (NT-3) or NT-3 and CNTF could produce substantial therapeutic effects in pmn (progressive motor neuropathy) mutant mice after intramuscular injection of the NT-3 or NT-3 and CNTF adenoviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Besides cancer vaccines, it is envisioned that this particular design may have utility in tissue engineerhCMV-IE promoter-containing DCCMV vector, which combines the principles of double-copy and IRES vector ing applications where the intent is to implant polymer encapsulated cell lines genetically engineered to continudesigns, 21,35 reproducibly directed high stable levels of exogenous gene expression in a panel of four human ously secrete pharmacological levels of bioactive proteins. 43,44 For such applications, it may be advantageous melanoma cell lines.…”
Section: Resultsmentioning
confidence: 99%